HYPOTHYROIDISM - Mamaraximov Nursulton Alisherovich,; Fayziyeva Dilshoda Ozod qizi,; Normuradov Alisher Ismailovich, (TADQIQOTLAR, 2026)
Annotation:  hypothyroidism  (  called  low  thyroid,  low  thyroid,  or hypothyroidism)  is  a  disorder  of  the  endocrine  system  that  produces  thyroid hormone.nnotation:  hypothyroidism  (  called  low  thyroid,  low  thyroid,  or hypothyroidism) is a disorder of the endocrine system that produces thyroid hormone. In this, it can cause snnotation: hypothyroidism ( called low thyroid, low thyroid, or hypothyroidism) is a disorder of the endocrine system that produces thyroid hormone. In this, it can cause symptoms such as a feeling of tiredness , decreased workload, depression. From time to time, the front of the neck can become larger due to the bulge. Untreated cases of hypothyroidism during pregnancy can lead to delayed growth and intellectual  development  in  infant  or  congenital  Iodine  Deficiency  Syndrome. Worldwide,  too  little  iodine  intake  in  the  diet  is  the  most  common  cause  of hypothyroidism.orldwide, too little iodine intake in the diet is the most common cause of hypothyroidism. The thyroiditis of the Japanese scientist Hashimoto is the cause of the most orldwide, too little iodine intake in the diet is the most common cause of hypothyroidism. The thyroiditis of the Japanese scientist Hashimorldwide, too little iodine intake in the diet is the most common cause of hypothyroidism. The thyroiditis of the Japanese scientist Hashimoto is theittle iodine intake in the diet is the most common cause of hypothyroidism. The thyroiditis of the Japanese scientist Hashimoto is the cause of the most common occurrence of hypothyroidism in countries where insufficient  iodine  is  not  required.  Less  common  causes  include  treatment  with radioactive  iodine,  an  injury  to  the  anterior  compartment  of  the  hypothalamus  or pituitary gland. The diagnosis of hypothyroidism, when suspected, can be confirmed by blood tests that measure Thyroid-Stimulating Hormone (TSH) and thyroxine levels. Salt  iodization  prevented  hypothyroidism  in  most  populations.  Thyroid  hormone replacement  with  levothyroxine  treats  hypothyroidism.  Medical  specialists  need  to adjust  the  dosage  according  to  the  symptoms  and  normalization  of  the  levels  of thyroxine  and  Thg.